Ghrelin Attenuates the Osteoblastic Differentiation of Vascular Smooth Muscle Cells through the ERK Pathway - Liang, Qiu-Hua; Jiang, Yi; Zhu, Xiao; Cui, Rong-Rong; Liu, Guan-Ying; Liu, Yuan; Wu, Shan-Shan; Liao, Xiao-Bo; Xie, Hui; Zhou, Hou-De; Wu, Xian-Ping; Yuan, Ling-Qing; et al. (PLOS ONE, 2012)
Vascular calcification results from osteoblastic differentiation of vascular smooth muscle cells (VSMCs) and is a major risk factor for cardiovascular events. Ghrelin is a newly discovered bioactive peptide that acts as a natural endogenous ligand of the growth hormone secretagog receptor (GHSR). Several studies have identified the protective effects of ghrelin on the cardiovascular system, however research on the effects and mechanisms of ghrelin on vascular calcification is still quite rare. In this study, we determined the effect of ghrelin on osteoblastic differentiation of VSMCs and investigated the mechanism involved using the two universally accepted calcifying models of calcifying vascular smooth muscle cells (CVSMCs) and beta-glycerophosphate (beta-GP)-induced VSMCs. Our data demonstrated that ghrelin inhibits osteoblastic differentiation and mineralization of VSMCs due to decreased alkaline phosphatase (ALP) activity, Runx2 expression, bone morphogenetic protein-2 (BMP-2) expression and calcium content. Further study demonstrated that ghrelin exerted this suppression effect via an extracellular signal-related kinase (ERK)-dependent pathway and that the suppression effect of ghrelin was time dependent and dose dependent. Furthermore, inhibition of the growth hormone secretagog receptor (GHSR), the ghrelin receptor, by siRNA significantly reversed the activation of ERK by ghrelin. In conclusion, our study suggests that ghrelin may inhibit osteoblastic differentiation of VSMCs through the GHSR/ERK pathway.